Profesor Dr. José Manuel Rivero Carvallo: un gigante universal y mexicano de la semiología cardiovascular - Andrés R. Pérez-Riera; Raimundo Barbosa-Barros; Maurício da Silva-Rocha; Rodrigo Daminello-Raimundo; Luiz C. de Abreu; Kjell Nikus (Archivos de Cardiología de México, 2023)
Professor Dr. José Manuel Rivero Carvallo (Fig. 1) was an eminent Mexican cardiologist, born in the state of Puebla on April 1, 1905, and died on February 15, 19931.